Quality management of short courses at higher education institutions in South Africa - Brits, Maria Magretha (My University, 2013)
This study is an attempt to conceptualise and enhance the quality management of the short course offerings at the Vaal University of Technology (VUT). The Higher Education Quality Committee (HEQC) conducted its first cycle of institutional audit exercises from 2004 – 2009 at private and public universities in South Africa. This study follows on the HEQC audit panel’s report, with reference to VUTs offering of short courses (SCs). The HEQC informed the institution that the quality assurance system of SCs is not on par with the requirements of the HEQC. Therefore, it does not meet the minimum standards for an effective quality management system for SCs. It is imperative for the institution to conceptualise the quality management of SCs and to develop a system that ensures ongoing improvement. This study addresses this gap by conceptualising the quality management of SCs on national level in higher education. The study draws on good practices on national level that can inform the refinement of the existing quality assurance system for SCs at VUT. The empirical study was conducted with public institutions of higher learning in South Africa. Quantitative data were collected from dedicated SCs and/or quality assurance or quality management offices at all 23 public institutions of higher learning. Five universities were identified as institutions with good practice, based on quantitative information that was gathered, analysed and interpreted during this study. The study revealed that it is imperative for higher education institutions to develop quality assurance systems that are based on cyclical processes of ongoing improvement, such as the PDCA (Plan-Do-Check-Act), PIRI (Plan-Implement- Review-Improve) and ADRI (Approach-Deployment-Results-Improvement) models. A key assumption of the research is that quality assurance for SCs at VUT should be aligned with the institution’s quality assurance system. The study highlights the value of the principles of Total Quality Management, the notion of continuous improvement, self-evaluation and external monitoring. Recommendations in this study suggest that VUT should conduct further institutional benchmarking exercises with the five institutions that received commendations and full delegations, in order to develop a conceptual model for understanding and enhancing its SC offerings.
M. Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology
Keywords: Higher Education Quality Committee; Quality assurance for Short Courses; Quality assurance systems; Vaal University of Tecnology Short Courses; 378.170968; Higher education institutions.; Education, Higher -- Standards